Measuring Women’s Economic Empowerment in Payment Projects : A Short Module to Complement Context-Specific Measures - World Bank (Washington, DC, 2022)
Cash transfers and digital payments hold promise for women’s economic empowerment through their potential to enhance women’s privacy, financial autonomy, decision making and labor force participation. Yet, despite this potential, gaps in data and evidence persist. This brief aims to provide actionable advice on measurement for project teams working on digital government-to-person (G2P) projects, as well as practitioners and researchers working on cash transfer payments and financial inclusion more broadly. It is not meant to serve as a comprehensive guide to women’s economic empowerment. Instead, the brief provides short measures focused on key outcomes related to women’s economic empowerment as a complement to more in-depth context-specific measures. The indicators suggested in this guide can be used for measurement in impact evaluations, monitoring and evaluation, or general population descriptions.